Adolescent Future Orientation in Non-Formal Educational Settings: A Preliminary Study of Santri in Pesantren Salafiyah - Dwi Nur Rachmah; Wiwin Hendriani; Primatia Yogi Wulandari (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Adolescent future orientation plays a crucial role in educational engagement, goal setting, and preparation for adulthood. Although future orientation has been extensively researched among adolescents in formal schools, research on this construct among students in Salafiyah Islamic boarding schools, as a representation of religion-based non-formal education, remains very limited. Addressing this gap is important for understanding how adolescents in alternative educational settings construct future aspirations and plans. This preliminary study employed a mixed-method descriptive exploratory design. Data were collected from 44 santri using questionnaires comprising closed- and open-ended questions. Quantitative data were analyzed using descriptive statistics, while qualitative responses were examined through thematic analysis. Findings show that (1) 97.8% of students often think about the future and consider education and family/community environment to affect their future; (2) career aspirations are dominated by entrepreneurs (36.4%), teachers (20.4%), and religious professions (13.6%); (3) thematic analysis yields five main themes: conceptualization of the future, future goals, outlook on the future, preparation strategies, and influencing factors. Even though they study outside the formal system, students actively build future aspirations and demonstrate directed educational planning, so it is important to integrate future-oriented pedagogical practices, career guidance, and goal-setting activities in non-formal educational institutions. Keywords: adolescent future orientation, educational aspirations, islamic boarding schools, non-formal education, preliminary study